The Implementation of Science Process Skills in Grade 5 IPAS Learning: A Case Study in Banda Aceh - Fira, Nessa; Oviana, Wati; Jannah, Misbahul; Nurdin, Syahidan; Wan Husin, Wan Nor Fadzilah (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2026)
The Merdeka Curriculum positions science and social studies (IPAS) learning not only as mastery of content knowledge but also as the development of science process skills as a foundation for students’ scientific thinking. This study aims to describe the instillation of science process skills in elementary IPAS learning viewed from the planning and implementation stages and to identify challenges faced by teachers. This research employed a descriptive qualitative approach. The research subjects consisted of three fifth-grade teachers from three elementary schools in Banda Aceh. Data were collected through observation, structured interviews, and documentation and analyzed using descriptive qualitative techniques and percentage analysis. The results indicate that science process skills have been implemented in IPAS learning; however, their implementation has not been optimal. At the planning stage, science process skills were not systematically designed, particularly in investigation and data analysis aspects, while at the implementation stage science process skills were more evident through active student engagement. The challenges faced by teachers include limited instructional time, inadequate facilities and learning media, differences in students’ abilities, and difficulties in designing process-oriented assessments.